The Implementation of E-Picture Strip Story in English Writing - I. G. N. Arik Kusuma Putra; G. A. P. Supianti (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
In today’s digital era teachers get a challenge to increase students' creativity and motivation by using technology as a medium. The use of e-picture strip story as a technology-based media become one of the strategies to students in English writing. Picture strip story can help students’ develop critical thinking creativity in writing to create magnificent various text. This study aims to analyze the procedures used by the researcher in implementing e-picture strip story in writing class and analyze the challenges faced by students. This study uses qualitative research as a research method. The subjects of this study were class VIII at junior high school. Data were collected using an observation checklist and an interview guide. Both data collection methods allow triangulation of data to ensure data validity. The result of the data that has been collected is the procedure carried out by the researcher is to carry out three stages, namely; pre-activity, whilst-activity, and post-activity. Then, the other findings found there are three challenges that researchers and students face, namely; time management, material resources, and classroom atmosphere.